PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, IKLIM SEKOLAH DAN KOMITMEN PROFESIONAL GURU TERHADAP KINERJA GURU - Sri Yomila Putri; Marlina Yosi Yanti; Alfroki Martha (CV. Adiba Aisha Amira, 2024)
This research aims to examine the influence of the principal's transformational leadership style, school climate, and teacher professional commitment on teacher performance. The research method used is literature. The research results show that the principal's transformational leadership style has a positive and significant influence on teacher performance. School climate also has a positive and significant effect on teacher performance. Meanwhile, teacher professional commitment has the strongest influence on teacher performance compared to the other two variables. In addition, it was found that school climate acts as a mediator that strengthens the influence of the principal's transformational leadership style and teacher professional commitment on teacher performance. This research has the implication that to improve teacher performance, it is necessary to increase the transformational leadership style of school principals and create a conducive school climate, as well as strengthening teachers' professional commitment. School principals and policy makers are expected to be able to implement effective strategies to develop these three aspects in order to achieve improvements in the quality of education.